Molecular biology - Clark, David P. (Elsevier Academic Press, 2005)
"Clark effectively introduces basic concepts followed by more specific applications as the discussion evolves. He has included current research results and takes a thorough look at the medical, agricultural, and social aspects that shape modern-day molecular biology. This text is concisely written and beautifully illustrated in full color, to help student readers stay engaged and focused on understanding." "Molecular Biology covers a broad range of topics to reinforce that molecular biology is applicable to more than just human medicine and health, but also applies to veterinary medicine, evolution, agriculture, and biotechnology."--Jacket.